Type 2 diabetes risk gene Dusp8 regulates hypothalamic Jnk signaling and insulin sensitivity - Schriever, Sonja C; Kabra, Dhiraj G; Pfuhlmann, Katrin; Baumann, Peter; Baumgart, Emily V; Nagler, Joachim; Seebacher, Fabian; Harrison, Luke; Irmler, Martin; Kullmann, Stephanie; Corrêa-da-Silva, Felipe; Giesert, Florian; et al. (The Journal of clinical investigation, 2020)
Recent genome-wide association studies (GWAS) identified DUSP8, encoding a dual-specificity phosphatase targeting mitogen-activated protein kinases, as a type 2 diabetes (T2D) risk gene. Here, we reveal that Dusp8 is a gatekeeper in the hypothalamic control of glucose homeostasis in mice and humans. Male, but not female, Dusp8 loss-of-function mice, either with global or corticotropin-releasing hormone neuron-specific deletion, had impaired systemic glucose tolerance and insulin sensitivity when exposed to high-fat diet (HFD). Mechanistically, we found impaired hypothalamic-pituitary-adrenal axis feedback, blunted sympathetic responsiveness, and chronically elevated corticosterone levels driven by hypothalamic hyperactivation of Jnk signaling. Accordingly, global Jnk1 ablation, AAV-mediated Dusp8 overexpression in the mediobasal hypothalamus, or metyrapone-induced chemical adrenalectomy rescued the impaired glucose homeostasis of obese male Dusp8-KO mice, respectively. The sex-specific role of murine Dusp8 in governing hypothalamic Jnk signaling, insulin sensitivity, and systemic glucose tolerance was consistent with functional MRI data in human volunteers that revealed an association of the DUSP8 rs2334499 risk variant with hypothalamic insulin resistance in men. Further, expression of DUSP8 was increased in the infundibular nucleus of T2D humans. In summary, our findings suggest the GWAS-identified gene Dusp8 as a novel hypothalamic factor that plays a functional role in the etiology of T2D.
Keywords: Hypothalamus; signální transdukce; Signal Transduction; Diabetes Mellitus, Experimental; hypothalamus; Insulin Resistance; experimentální diabetes mellitus; zvířata; myši; Mice; Diabetes Mellitus, Type 2; myši knockoutované; Diabetes; Metabolism; Mice, Knockout; inzulinová rezistence; fosfatasy s dvojí specifitou; Obesity; Animals; MAP Kinase Kinase 4; Dual-Specificity Phosphatases; diabetes mellitus 2. typu; MAP kinasa-kinasa 4